Between cross and Resurrection : a theology of Holy Saturday - Lewis, Alan E. (Alan Edmond), 1944- (Michigan : Grand Rapids : William B. Eerdmans Publishing Company, 1994)
"For much of Christian history the church has given no place to Holy Saturday in its liturgy or worship. Yet the space dividing Good Friday and Easter may be the best place from which to reflect on the meaning of Christ's death and resurrection. This superb work by the late Alan Lewis develops on a grand scale and in great detail a theology of Holy Saturday." "The first comprehensive theology of Holy Saturday ever written, Between Cross and Resurrection shows that at the center of the biblical story and the church's creed lies a three-day narrative. Lewis explores the meaning of Holy Saturday - the restless day of burial and waiting - from the perspectives of narrative (hearing the story), doctrine (thinking the story), and ethics (living the story). Along the way he visits as many spiritual themes as possible in order to demonstrate the range of topics that take on fresh meaning when viewed from the vantage point of Holy Saturday."--Jacket.
Part 1 Hearing the Story -- Part 2 Thinking the Story -- Part 3 Living the Story.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Three days in the tomb; Holy Saturday